THE URGENCY OF INDONESIA'S NATIONAL FOOD SELF-SUFFICIENCY FROM A SUSTAINABLE NON-MILITARY DEFENSE ECONOMICS PERSPECTIVE - K.P. Suharyono S. Hadiningrat; Fitry Taufiq Sahari; Trismawan Djonisajoko; Teguh Yuwono (Yayasan Inspirasi Merah Putih Indonesia, 2026)
Contemporary geopolitical dynamics have shifted the national-security paradigm toward economic resilience. Non-military threats, particularly disruptions to global supply chains and climate-related shocks, require Indonesia to accelerate food self-sufficiency. This study analyzes budget efficiency, identifies operational gaps, and evaluates civil-military collaboration in the new-rice-field development program during 2025–2026. A mixed-methods approach combines qualitative analysis of thematic audit and policy documents with quantitative evidence from farmer surveys and selected production and budget indicators. The qualitative findings indicate that hybrid collaboration between agricultural extension officers and the Indonesian National Armed Forces at the village level can operate as a force multiplier by shortening bureaucratic chains and supporting a more accountable logistics ecosystem. However, program sustainability is constrained by weak initial spatial-data validity, reflected in Survey, Investigation and Design (SID) contracting of only 32%, as well as limitations in micro-irrigation networks. Importance Performance Analysis (IPA) places wetland water management and subsidized diesel supply for agricultural machinery in Quadrant I as the main priorities. Cost-Benefit Analysis (CBA) nevertheless indicates that the IDR 8.75 trillion investment in new rice fields outside Java is economically efficient, with a Benefit-Cost Ratio (BCR) of 1.30. The study recommends stronger penta-helix collaboration, digitally integrated agrarian data, and reinforcement of a maritime food-security belt.